Listening to the noise: On price efficiency with dynamic trading - Lutz Arnold; David Russ (Deutsche Bundesbank, 2024)
This paper shows that, in the canonical dynamic rational expectations equilibrium model, public information about future noise trading is potentially detrimental to contemporaneous price efficiency. Our result supports concerns that social sentiment investing, sparked by growing availability of big data and advances in the way of processing it, exacerbates, rather than ameliorates, the negative impact of noise trading on price efficiency.
Keywords: G12; G14; 330; social sentiment investing; price efficiency; noise trading; information aggregation